Predictor in Influencing Indonesian Consumers Purchase Intention towards Green Shampoo and Soap - Almira Mandasaria; Arnold Edricka; Bima Prasetyaa; Riandy Yohannes Saputra; Yostina Dian Anggraini; Istijanto Istijanto (Indonesian Business Review, 2021)
This research’s purpose is to inspect the aspects, which may determine green soap and shampoo purchase decisions among consumers in Indonesia. Shortage of environmental consciousness observed from consumers in Indonesia has stimulated the curiosity to continue this study. With support from organized opinion polls, data were accumulated from a total of 320 people of consumers in Indonesia. Outcome of the accumulated data reflects some crucial factors for green shampoo and soap purchase intention, for example, environmental consciousness, eco-label, and attitude. Contrary to the hypothesis, advertisement, price, social influence and recycle participation was not a crucial influence of green shampoo and soap purchase intention of Indonesian citizens. The inferences of these revelations and bearings for future examination are given toward the finish of this paper. This research presents experiential comprehensions refer to the common perspective of an Indonesian markets on the determinants of green shampoo and soap purchase decision among vast range of age.